Allozyme polymorphism in tetraploid potato gene pools and the effect of human selection - Ortíz, R.; Hauman, Z. (Springer, 2001)
The need for broadening a crop’s genetic base may be determined by comparing allele frequencies within the gene pools of farmer selections in their centers of diversity with that of modern breeding populations. The genetic structure of Andean and Chilean potato farmer selections was investigated with the aid of nine isozymes, which have been studied in detail and used to characterize North American cultivars and advanced breeding lines. These isozymes are associated with the most-important agronomic or quality characters in the North American gene pool. By comparing these data with previous analyses of the North American gene pool, allozyme frequency changes for nine loci were monitored. Allozyme frequency changes were not always due to genetic drift, but resulted also from directional selection of isozyme marker linked quantitative trait loci (QTLs) affecting agronomic or quality characters. Changes in allozyme frequency can also occur as a consequence of pleiotropy, i.e. the isozyme itself may be involved in the expression of a phenotype. These allozyme frequency changes may reflect the manipulation of the potato genome by breeders. There were allozymes in some North American cultivars that were not observed in the farmer selections from the Andes and Chile. This confirms that breeders have already introgressed exotic genes from wild and other primitive cultivated tuber-bearing Solanum species. On this basis, the need for broadening the genetic base for specific chromosomes (or chromosome regions) should be based on analysis with these and other genetic markers available in potato.